تقييم اختلاطات جراحة الجيوب التنظيرية بالطرق الجراحية المتعددة (خبرة مشفى الأسد الجامعي في اللاذقية بين عامي2012-2013 ) - يوسف, يوسف; عيسى, جورج; عيسى, نانسي (Latakia University Journal -Medical Sciences Series, 2014)
قمنا في مشفى الأسد الجامعي في اللاذقية وخلال الفترة الممتدة من شباط 2012 وحتى أيلول 2013 بدراسة عينة عشوائية مكونة من 60 مريضاً ( ذكوراً وإناثاً) ممن أجريت لهم جراحة جيوب تنظيرية والذين قسموا لمجموعتين: المجموعة الأولى ضمت 45 مريضاً أجريت لهم الجراحة التنظيرية التقليدية (بدون استخدام جهاز الملاحة) المجموعة الثانية ضمت 15 مريضاً أجريت لهم الجراحة بالاستعانة بجهاز الملاحة تم تحديد نسبة الاختلاطات في كل مجموعة وكانت(55.56%) للمجموعة الأولى و(20%) للمجموعة الثانية , توزعت هذه الاختلاطات بين اختلاطات كبرى (13.33%) أكثرها حدوثا" كان انعدام الشم , واختلاطات صغرى (33.34%) أكثرها حدوثا" كان النزف. بالمقارنة بين نتائج المجموعتين تبين أن أكثر الاختلاطات حدوثا"كانت اختلاطات صغرى وشملت النزف الموضعي والالتصاقات بنسب مختلفة النزف (33.3%) بالجراحة بدون استخدام جهاز الملاحة مقابل (13.3%)عند الاستعانة بالجهاز أما الالتصاقات فكانت (31.1%) بالجراحة بدون استخدام الجهاز مقابل (6.7%) عند الاستعانة بالجهاز ولم تشاهد أية اختلاطات أخرى في الجراحة مع جهاز الملاحة مما يظهر الدور الكبير له في تقليل الكثير من الاختلاطات التي ظهرت بالجراحة التقليدية. We conducted a study in Assad University Hospital in Lattakia during the period of February 2012 until septemper 2013 . The study encompassed a random sample of 60 patients (males and females) who conducted them Endoscopic sinus surgery, which was distributed into two groups: the first group included 45 patients who underwent traditional ESS ,The second group included 15 patients who underwent surgery with the help of navigation device. Complications were determind in each group as (55.56% ) for the first group and )20%) for the second group , those complications were distributed to (13.33%) as major complications the most frequent " was breach of the lamina papyracea , and (33.34%) as minor complications the most frequent " was hemorrhage A comparison between the results of the two groups shows that more frequent complications were minor complications included local hemorrhage and adhesions in different percentages: Hemorrhage (33.3%) traditional surgery compared to (13.3%) when using a navigation device.The adhesions were ( 31.1% ) traditional surgery compared to (6.7%) when using navigation device. No other complications were happening in surgery with a navigation device , which shows a significant role in reducing many of the complications that have emerged traditional surgery .